Are Zero-Rating Practices in the Public Interest? A Set of Case Studies - Scott Jordan (International Telecommunications Society (ITS), 2018)
Zero-rating and associated throttling practices by broadband Internet access service providers are widely debated. We evaluate three types of such practices. We find that sponsored data programs are likely in the public interest if and only if the price charged is reasonable and not unreasonably discriminatory. In contrast, we find that zero-rating and throttling of video streaming is not in the public interest, because it constitutes application-specific throttling and is not reasonable network management. We also find that free mobile Internet access to specific edge providers is likely not in the public interest, because it likely unreasonably interferes with or disadvantages end-users or edge providers.
Keywords: 330